Genetic and metabolic structure of bacterial communities in cerrado soil under different managements - de Souza, Leandro Moraes; Schlemmer, Franciele; Alencar, Priscila Martins; Lopes, André Alves de Castro; Passos, Samuel Ribeiro; Xavier, Gustavo Ribeiro; Fernandes, Marcelo Ferreira; Mendes, Iêda de Carvalho; Reis Junior, Fabio Bueno dos (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the metabolic and genetic structure of bacterial communities in a cerrado Oxisol under native vegetation or cultivated in a soybean/maize rotation system under conventional tillage and no tillage. EcoPlate microplates were used to determine the metabolic profile and diversity of bacterial communities, and denaturing gradient gel electrophoresis (DGGE) to assess the genetic structure. The Mantel statistic test was used to evaluate the relationship between the metabolic and the genetic structure. The bacterial community under native vegetation showed a different metabolic profile than that of cultivated soils. In the area cultivated with soybean under conventional tillage, the carbon source utilization pattern differed from the other treatments. Based on the DGGE results, the bacterial community under native vegetation showed 35% similarity to the ones found under cultivation. Distinct groups of soil bacterial communities were formed between the areas under conventional tillage and no tillage. A significant correlation of 62% was observed between matrices generated by EcoPlate microplates and by DGGE. Variations in the metabolic profile are related to changes in the genetic structure of soil bacterial communities.